Assessing the influence of hydrogen on texture evolution in polycrystalline nickel deformed under uniaxial tension. (November 2020) - Harris, Zachary D.; Ritzo, Michael A.; Schulte, Justine M.; Agnew, Sean R.; Burns, James T.
Abstract: Uniaxial tensile experiments on hydrogen-charged and non-charged polycrystalline nickel deformed to a true plastic strain of 0.1 at room temperature and 77 K reveal that hydrogen has no measurable effect on texture evolution. Texture measurements were completed on samples of each condition, as well as an as-received reference specimen, using electron backscatter diffraction data collected from >20, 000 individual grains. Crystal plasticity simulations support the conclusion that the similarity is attributable to the insensitivity of small-strain deformation texture evolution to potential hydrogen-induced modifications in deformation mechanisms. Graphical abstract: Image, graphical abstract